2010
DOI: 10.7150/ijms.7.94
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the long-term response to tacrolimus in renal transplant patients: Pharmacokinetic and pharmacogenetic approach

Abstract: Background: The aim of our study was to determine the impact of CYP3A5*1 and CYP3A5*3 on the kinetics of tacrolimus in renal transplant recipients.Material and methods: Forty kidney recipients were selected to participate. Maintenance scheme consisted of tacrolimus, a purine inhibitor and a steroid. CYP3A5 genotyping was performed with PCR and RFLP. Pharmacokinetic model was developed with Linear Regression and General Linear Model repeated measures approach. The impact of sex, CYP3A5*1 allele, age at transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…The results were analyzed to provide estimates of tacrolimus CL/F and V/F using a population pharmacokinetic approach. 2,25 Many factors, including physiology, pathology, lifestyles, food habits, gender, body weight, and drug coadministration can affect the pharmacokinetics of tacrolimus, 26,27 and as such, it has a large range of interindividual and intraindividual pharmacokinetic variabilities. 22 In this study, the typical values were as follows: CL/F with IIV was 20.9 LÁh 21 (23.8%), median daily dose was 4 mg, hematocrit was 34.58%, total serum protein was 66.42 g/L, which is close to previous reports in adult white patients and South Korean and Chinese patients using tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…The results were analyzed to provide estimates of tacrolimus CL/F and V/F using a population pharmacokinetic approach. 2,25 Many factors, including physiology, pathology, lifestyles, food habits, gender, body weight, and drug coadministration can affect the pharmacokinetics of tacrolimus, 26,27 and as such, it has a large range of interindividual and intraindividual pharmacokinetic variabilities. 22 In this study, the typical values were as follows: CL/F with IIV was 20.9 LÁh 21 (23.8%), median daily dose was 4 mg, hematocrit was 34.58%, total serum protein was 66.42 g/L, which is close to previous reports in adult white patients and South Korean and Chinese patients using tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus was given twice a day in individually adjusted doses and its trough levels were measured 12 h post dose. The authors have found that CYP3A5*1 variant was associated with significant lower tacrolimus dose adjusted concentration at 3, 6, 12 and 36 months after transplantation, and that carriers of CYP3A5*1 allele had lower predicted measures for tacrolimus dose adjusted concentration and higher predicted measures for volume of distribution [78]. The frequency of CYP3A5*1 allele was 6.3% and the prevalence of CYP3A5 expressors was 12.5%.…”
Section: Cyp3a5mentioning
confidence: 94%
“…In 2010, Katsakiori and colleagues investigated the impact of CYP3A5*1 and CYP3A5*3 alleles on the kinetics of tacrolimus in 40 renal transplant recipients [78]. Tacrolimus was given twice a day in individually adjusted doses and its trough levels were measured 12 h post dose.…”
Section: Cyp3a5mentioning
confidence: 99%
“…Caution must be taken when extrapolating these results to other species since it is well established that important variability regarding tacrolimus biodisponsibility exists within species, individuals, and even intraindividually (51). Further research in the rat and other animal models of UTx must be conducted, and these experiments should also include tests of pregnancy potential.…”
Section: Discussionmentioning
confidence: 95%